The Effect Of Counterpressure With A Birthball On Reducing Labor Pain During The First Active Phase - Rohaya, Rohaya; Ana Persari, Devy; Novita, Nesi; Wahyuni, Sari; Jamila, Jamila; Kamalia, Rita (NHM PRESS, 2024)
Most births are always accompanied by intense pain and sometimes cause trauma to the birth mother. Efforts to relieve pain and provide comfort for mothers giving birth non-pharmacologically include using counterpressure with a birth ball. The research aimed to determine the effect of counterpressure with a birth ball on reducing labor pain during the first active phase. This research design is a pre-experiment with a one-group pretest-posttest design. The total sample was 30 mothers in the first stage of labor. Data collection techniques used a counterpressure questionnaire with a birth ball and a VAS pain scale. Data analysis used paired t-test. The pain scale in the group before treatment averaged 7.94 and after treatment averaged 6.41. The results of data analysis using the paired t-test showed statistically significant results, P Value = 0.000 < 0.05. There is an effect of giving counterpressure with a birth ball on reducing labor pain in the active phase of the first stage. It is hoped that health workers can apply counterpressure with this birth ball as a method of reducing pain.